Aluminum-doped NiO nanofibers as chemical sensors for selective and sensitive methanol detection. Issue 5 (11th January 2019) - Feng, Changhao; Jiang, Zhongwei; Chen, Bin; Cheng, Pengfei; Wang, Yinglin; Huang, Chengzhi
Abstract : One-dimensional nanomaterials with controlled morphology have received considerable attention as chemical sensors. Abstract : One-dimensional nanomaterials with controlled morphology have received considerable attention as chemical sensors. Herein, we report a low-cost and facile method for manufacturing chemical sensors based on Al-doped NiO nanofibers. The structures and morphologies of the samples were characterized by SEM, TEM, SAED and XRD. Chemical sensors with 3 mol% Al-doped NiO nanofibers showed a response of 10.4 to 200 ppm methanol. The transient, dynamic, repeatability, selectivity, and long-term stability characteristics of the obtained sensors were tested, which indicated that these chemical sensors were promising for detecting methanol vapor in air.